Nursing Students' Satisfaction Regarding Clinical Learning Environment at Liaqat College of Nursing for Female (Journal of Asian Development Studies, 2024)
The clinical learning environment is where nursing students gain hands-on experience and apply their academic knowledge in real-world healthcare environments. The clinical learning environment is a complex system of components within a healthcare facility that influence learning outcomes. A cross-sectional study was conducted between February and March 2024 at Liaquat College of Nursing in Jamshoro, Sindh, Pakistan. The study population included Generic BSN students in their first, second, and third years. BSN Generic students who wanted to take part in this study were included. Data was collected using a non-randomized convenience sampling technique. The intended sample size was 70 nursing students selected from Liaquat College of Nursing for Female in Jamshoro. The results reveal that most BSN Generic students "agreed" with the statement that the "clinical instructor was competent and about his/her skills", with a percentage of 51.4%. Overall, the findings indicate that the clinical learning environment is satisfactory. In addition, students were satisfied with the competency of the clinical instructor, and the findings also concluded that patients in healthcare settings are adequately cared for by healthcare providers. Satisfaction in clinical settings often correlates with a deeper understanding of nursing practices. Students are more likely to engage actively, when they are content with their clinical experiences.